Incidence and outcome of no flow after primary percutaneous coronary intervention in acute myocardial infarction - Datta, Goutam (Journal of Cardiology and Cardiovascular Medicine, 2020)
Background: Primary percutaneous coronary intervention (PCI) of the infarct-related artery (IRA) is the most effective treatment modality in ST-segment elevation myocardial infarction (STEMI). Incidence of no flow is 8.8% - 10% in primary PCI of STEMI patients. Our aim was to study actual incidence and outcome of no flow patients. Methods: Five hundred and eighty primary PCI patients were enrolled and evaluated from 2016 January to 2017 December. We used drug eluting stents in all cases. Majority of our patients (> 90%) presented to emergency six hours after onset of symptoms. There were many patients where there was no flow even after mechanical thrombus aspiration and pharmacological vasodilator therapy. We have studied primary outcome (mortality) of no flow in those patients. Results: There were 44 cases of no flow in our series (7.75%). Involvement of Left anterior descending artery (LAD) was in eighteen patients. Right coronary artery (RCA) was culprit in twenty four cases. Only two cases were seen in LCX territory. One month mortality rate in no flow group was 50% and 6.25% in successful recanalization group. One year mortality was 12.5% in successful recanalization group and 66% in no flow group. Conclusion: Refractory no flow during STEMI intervention is associated with increased incidence of major adverse cardiovascular events (MACE). There is no established strategy to solve this phenomenon.